PENGENALAN DIVERSIFIKASI PRODUK HASIL PERIKANAN PADA IBU DAN BALITA SEBAGAI UPAYA PENINGKATAN GEMAR MAKAN IKAN UNTUK MENCEGAH STUNTING DI KB TK YAA BUNAYYA, SURABAYA - Patmawati; Sahidu, Adriana Monica; Subekti, Sri; Kurnia, Kiki Adi (Jurnal Abdi Insani, 2024)
Early childhood is the golden age of children's development to obtain an educational process and is also fundamental and strategic education in the development of human resources, therefore we, the Faculty of Fisheries and Maritime Affairs, Airlangga University, collaborate with Day Care- KB-PAUD and YAA BUNAYYA Kindergarten to carry out activities community service related to the introduction of diversified fishery products among mothers and toddlers as an effort to increase their interest in eating fish to prevent stunting. Day Care-KB-PAUD and TK YAA BUNAYYA is an educational institution for early pre-school age in Surabaya City, East Java Province with a total of 130 students and 25 teachers. Indonesia is a developing country that is still facing serious problems regarding stunting and improving nutritional status is a top priority, therefore having a community service program related to the introduction of fishery product diversification is one solution to increase fish consumption as a high protein intake to prevent stunting. In this community service activity, we introduce from an early age the importance of eating fish, the nutritional content, and the benefits obtained from consuming fishery products. The activities carried out were demonstrations distributing fish food products, providing education for children, parents and teachers about the importance of eating fish. Finally, we also share modules related to several types of fisheries food diversification which can be easily practiced at school or by parents at home